THE DEVELOPMENT OF E-MODULE BASED ON SCIENTIFIC APPROACH TO IMPROVE STUDENT LEARNING OUTCOMES IN WORK AND ENERGY MATERIALS - Manik, Luni Karlina; Wulandari, Dewi (IPER (Indonesian Physics Education Research), 2023)
This research aims to; (1) What is the level of validation of the development of physics e-module based on the scientific approach that was developed on the Work and Energy material. (2) How did the students respond to the electronic module (e-module) based on a scientific approach on the subject matter of Work and Energy for class X SMA/MA students. (3) How is the effectiveness of physics e-module teaching materials based on scientific approach on Work and Energy materials to improve student learning outcomes. This study uses research and development (R & D) methods. The development model in this study uses a 4D model learning tool development method that is limited to the 3D stage with Define, Design, and Development Steps. The data collection instruments used in this study consisted of: material expert and media expert validation questionnaires, teacher responses to questionnaires, student response questionnaires and test instruments. The type of data obtained from the research results is qualitative data which is analyzed using quantitative data in the form of numeric data and interpreted with guidelines for assessment category criteria to determine product quality. The results of this study are, (1) the scientific approach-based physics learning e-module assisted by work and energy materials, the results obtained get very valid criteria with an average validation score of 93% material experts, and 90% media experts, (2 ) Physics learning e-module based on a scientific approach on Work materials and energy the results obtained are very practical criteria with the average score for small group trials 92%, for large group trials 94% and for teacher response tests 90%. (3) physics e-learning module based on a scientific approach to material, Workand energy, the results obtained have a moderate level of effectiveness with an average N- gain score of 0.70.